Central Coast Pride gathering, Mission Plaza, 2017 (2017)
2017 Central Coast Pride event, also known as SLO Pride. The event takes place annually in the Mission Plaza in downtown San Luis Obispo. The Central Coast Queer Archives and Oral History Project (CCQAP) collected images from the event in order to tell the history of LGBTQ people locally.